THE EFFECT OF GOOD GOVERNANCE ON REGIONAL FINANCIAL MANAGEMENT TRANSPARENCY IN PONOROGO REGIONAL WORKING UNITS - Titin Eka Ardiana; La Ode Sugianto; Diana Pramudya Wardhani (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
This study was conducted to examine the effect of good governance on the transparency of regional financial management in the Ponorogo Regency Regional Work Unit. The object of this research is the Regional Apparatus Work Unit in Ponorogo Regency as the location for the implementation of regional financial management. The type of research conducted in this research is descriptive quantitative. The data used in this study are primary data. The data collection method used in this research is by distributing questionnaires directly. The sampling technique in this study uses the Purposive Sampling method. the number of samples taken as many as 145 respondents consisting of Head of Agency, Head of Finance, Financial Administration, Treasurer, Head of Accounting, Finance Secretary. Information regarding the variables in this study was obtained from respondents who were transferred in the form of numbers and then analyzed with the SPSS program. The analysis used is simple regression. The results of this study are the Good Governance variable has a positive and significant effect on the transparency of regional financial management in Ponorogo Regency. This means that the better the governance (good governance), the more transparent regional financial management will be. This shows that good governance is able to affect the transparency of regional financial management by 8.6% and the remaining 91.4% is influenced by other factors not included in the model. Keywords: Good Governance, Regional Financial, Management Transparency